POTENTIAL USE OF ORGANIC MINERAL AS MINERAL SOURCE FOR DIET OF JUVENILE VANNAMEI SHRIMP, Penaeus vannamei - Asda Laining; Rachman Syah; Muslimin Muslimin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
The use of organic mineral (OM) has been recently introduced in aquaculture both as feed supplement and water quality improvement. A feeding experiment was conducted to evaluate a response dose of OM on growth, survival, and mineral content in whole the body and carapace of vannamei shrimp (Penaeus vannamei). Three diets were supplemented with different levels of organic mineral at 1 (OM1), 2 (OM2) and 4 (OM4) g/100 g diet. Positive control was a diet without OM inclusion but supplemented with commercial mineral mixture at level of 4 g/100 g diet. Juvenile vannamei shrimp with average initial body weight of 3.5±0.1 g were stocked into 12 tanks with a capacity of 200 L. After 75 days feeding trial, highly significant weight gains was observed in shrimp fed OM at all levels compared to the positive control. However, no significant differences were found among dietary OM groups. The growth response was clearly shown by the same values of SGRs in the three OM supplemented groups (1.1%/d) and only differed significantly from positive control. Increasing of dietary OM significantly improved survival rate of shrimp where the highest was observed in group fed OM1 and the lowest was in control diet. Effect of dietary OM on whole body Ca and P were quite similar while whole body Ca and P content of OM1 group was slightly high and tended to decrease in two groups with higher level dietary OM. However, no significant differences among the treatment groups. A clear response of supplementing OM in diet was detected on whole body Zn content. Increase of dietary OM resulted in an increase of Zn content in whole body. The effect was clearly shown when diet contained 2% and 4% OM. Carapace Ca content was highly significant when diet contained 2% OM. Similar to whole body Zn content, there was also a linear trend of response dose of dietary OM on carapace Zn content which the highest was found in dietary OM4. Based on growth, survival rate, and Zn content in whole body and carapace, dietary OM at 1 g/100 g diet can replace mineral mixture as mineral source in diet of vannamei shrimp.